2023
DOI: 10.1371/journal.pone.0287969
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptome profiling provides insights into rhizome enlargement in ginger (Zingiber officinale Rosc.)

Abstract: The rhizome is an economically important part of ginger (Zingiber officinale Rosc.). However, the mechanism of ginger rhizome enlargement remains unclear. In this study, we performed an integrated analysis of the hormone content and transcriptome of ginger at three rhizome enlargement stages: initial enlargement (S1), middle enlargement (S2), and peak enlargement (S3). With rhizome enlargement, the levels of the hormones zeatin (ZT), gibberellic acid (GA), indole acetic acid (IAA), and jasmonic acid (JA) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that indole-3-acetic acid (IAA) exists in a dynamic balance in plants, and its content and distribution in the roots directly determine cell division [ 7 ]. In Zingiber, the levels of the hormones such as IAA, gibberellic acid (GA), and jasmonic acid (JA) were significantly increased with increasing rhizome diameter [ 8 ]. However, the role of IAA in root formation remains contentious.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that indole-3-acetic acid (IAA) exists in a dynamic balance in plants, and its content and distribution in the roots directly determine cell division [ 7 ]. In Zingiber, the levels of the hormones such as IAA, gibberellic acid (GA), and jasmonic acid (JA) were significantly increased with increasing rhizome diameter [ 8 ]. However, the role of IAA in root formation remains contentious.…”
Section: Introductionmentioning
confidence: 99%